The Effect of Whistleblowing and Professional Skepticism on Fraud Detection Fraud and Fraud Audit Training as a Moderating - Waromi, Juliana - (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2024)
We surveyed to examine fraud detection. Specifically, we investigate the impact of whistleblowing and professional skepticism on fraud detection by using moderating fraud audit training. All of the respondents were auditors working for the Supreme Audit Institution Representative of Papua Province in Indonesia. Using a census sampling method. The data collection technique used an instrument through a questionnaire. A total of 40 auditors participated in this study. The application of moderated regression analysis (MRA) approach for data analysis. The findings indicate that whistleblowing and professional skepticism have a significant influence on fraud detection. Analyzing the moderating variables of fraud audit training does not strengthen professional skepticism and fraud detection. The implications of our results for internal and external audits of government enhance professional skepticism through fraud audit training and using whistleblowing information.